How to promote preservice teachers’ reflections through critical incident training - Anselmann, Veronika (Frontiers in Education, 2023)
This study with a pre-post design reports the results of training developed from the framework of reflective practice and the critical incident technique (CIT) for teacher education. Fiftythree preservice teachers participated in either online or face-to-face training, with the aim of determining if the training sufficiently improved their reflection abilities. To this purpose, an online questionnaire with validated scales on educational satisfaction, reflection abilities, and learning logs were used. The data were analyzed using descriptive statistical analysis and ttests, as well as qualitative data analysis. The results show that the students significantly improved their teaching reflection abilities after participating in the training. Giving preservice teachers the opportunity to reflect on their own experiences is thus an appropriate way to foster their reflection abilities.